THE INFLUENCE OF SERVICE QUALITY AND UNDERSTANDING OF TRI-NGA TAMANSISWA’S ON THE INTENTION TO COMPLY WITH PROSPECTIVE TAXPAYERS - Wardani, Dewi Kusuma; Wulandari, Eka Feby (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Tax compliance intention is the human desire to act tax compliant. The level of taxpayer compliance in reporting and paying taxes has tended to increase in the last five years. The large contribution of taxes in the development and financing of the country, resulting in the Directorate General of Taxes continues to strive to optimize and maintain tax revenues to remain within the set target. Tax compliance intention can be improved through several factors such as service quality and understanding of the Tamansiswa tri-family. The purpose of this study was to analyze the effect of service quality and understanding of the tri-nga Tamansiswa. This study uses a quantitative approach with a sample of 112 respondents as primary data, using SPSS version 20. The findings in this study indicate that service quality and understanding of tri-nga Tamansiswa have a positive effect on the intention to comply with prospective taxpayers.